Detection of antibiotic resistant Avibacterium paragallinarum from broiler chickens in Bangladesh - Khatun, Mst. Mousumi; Lijon, Md. Bakhtiar; Islam, Md. Ariful; Sultana, Nasrin (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: An attempt was undertaken for the detection and characterization of Avibacterium paragallinarum from clinically sick broiler chickens during field outbreaks. Materials and methods: Nasal and ocular discharges (n=6), tracheal swab (n=6), tracheal washing (n=4) and infraorbital sinus exudates (n=4) were collected aseptically from broiler chickens (n=10). To isolate A. paragallinarum, the clinical samples were cultured onto blood agar and chocolate agar enriched with Nicotinamide Adenine Dinucleotide (NAD) and feeder organism (Staphylococcus aureus). Identification of A. paragallinarum was performed by Gram staining reaction, sugar fermentation profiles using five basic sugars (Dextrose, Maltose, Sucrose, Lactose and Mannitol) and biochemical tests (Indole, Voges Proskauer and Methyl red tests). Antibiogram of the bacterial isolates of infected chicken was performed against five antibiotics namely Ciprofloxacin, Azithromycin, Gentamicin, Ampicillin and Cefalexin using disk diffusion method. Results: Results of colonial morphology, Gram staining reaction, sugar fermentation and biochemical tests confirmed one isolate as A. paragallinarum. The overall prevalence of IC in broiler chicken was 10% (1 of 10). This isolate was found to be sensitive to Ciprofloxacin, Azithroycin and Gentamicin and resistant to Ampicillin and Cefalexin. Conclusion: This is the first report of detection of A. paragallinarum from broiler chicken in Bangladesh. http://doi.org/10.5455/javar.2016.c149